Knowledge, attitude and practices of reproductive age women towards female condoms at Kamuzu Central Hospital, Lilongwe. - Phensere, Julia B. (Kamuzu University of Health Sciences, 2022)
A study on knowledge, attitude and practices of women of the reproductive age towards female condoms was conducted in Lilongwe district at Kamuzu Central Hospital. The study objectives were to assess reproductive women's knowledge on female condoms, to assess the attitude of reproductive age women towards female condoms, to establish utilization of female condoms by reproductive age women in Lilongwe and to identify factors that hinder reproductive age women from utilizing female condoms. The methodology used in this research study was the qualitative method and a sample of 10 was used. In-depth interview guides developed by the researcher, were used to collect data. The results showed that women had some knowledge on female condoms. However, the knowledge was not adequate. The results also showed that women had misconceptions about Fc's; that the condom may get stuck in the stomach and cause diseases, also that the FC's case cervical cancer. The results also showed that most women had never used FC's before. Hindrances that were identified in regards to FC's use were; scarcity of FC's, and also that they are sold at a high price. In view of the findings of the study; the following recommendations were made to promote utilization of FC's. There's need for nurses to provide adequate information to women when disseminating information. Nurses as managers have to ensure continuous and enough supply of FC's at all times. Nurses as educators should take charge of education on FC's and should ensure that people, in this case women are well informed about FC's. The information about female condoms should be emphasized in schools where they do have the FC's as part of their curricula. Nurses should also update their knowledge on female condoms though research.